Modelling the transport mechanism of organic molecules into cell membranes: The role of organic solvents. (June 2022) - Casalegno, Mosè; Sello, Guido
Abstract: Substrate availability is a key issue in the process design for chemicals production through enzymatic reactions. In whole cell bioconversions, the introduction of an organic solvent provides an efficient and flexible way to control substrate availability. Although successful, this route has often been based on trial and error experiments, and very little is known about the role of the solvent in the whole process. Modeling the transport mechanism of substrate molecules into cell membranes and the solvent-membrane interaction represents a first step toward a better understanding of the mechanisms underlying bioconversion efficiency. Hereafter, we report and discuss the results of such a modeling activity, which we carried out by means of molecular dynamics simulations. To better approach real-world experimental settings, we explicitly accounted for the possibility of solvent stirring. Our results are in agreement with the experimental data, paving the way to the application of molecular modeling in this recent and fast growing area of organic syntheses. Graphical Abstract: ga1 Highlights: The role of solvent in substrate transport is a key issue in whole cell bioconversions. The hypothetical mechanisms of substrate transport are investigated by means of molecular dynamics simulations. Solvent acceleration is enabled to model stirring effects. For the investigated substrates, the transport mechanisms are qualitatively consistent with the available experimental data.